Liquefaction of natural rubber to liquid fuel using water and alcohol solvents / Nabeel Ahmad - Nabeel, Ahmad (2019)
Natural rubber is a renewable resource that can potentially be used to produce liquid fuels via liquefaction process. Natural rubber is a rich biomass resource in Malaysia, and it is therefore very important that it could be utilized for more beneficial purposes, particularly in the context of development of biofuels. In this study, natural rubber was characterized using TGA and elemental analysis to understand its thermal and chemical properties, then it was liquefied at low temperature using hydrothermal liquefaction technique to produce liquid fuels. Furthermore, to improve the quality and quantity of the oil, the different types of alcohols were used as a solvent to replace the water. For all mentioned processes, the effect of different parameters such as temperature, material to solvent ratio and time were studied. All the obtained liquid products were analyzed by various methods such as pycnometer, viscometer, pH meter, FTIR, GCMS, and elemental analysis. Several important findings were also discussed in this study including potential energy recovery from natural rubber and energy consumption ratio study. In addition, the techno-economic study also provided in this thesis for feasibility assessment of the liquefaction of natural rubber using water and propanol as a solvent.